The determinants of consumption poverty in Fitche Town of Oromia Regional State, Ethiopia - Getachew M. Kumssa (Cogent Social Sciences)
Poverty is the most devastating global problems catching the attentions of development scholars. The issue of poverty was enshrined in the first goal of the Millennium Development Goals and the Sustainable Development Goals. This study was conducted on the determinants of consumption poverty in Fitche Town, Ethiopia, using cross-sectional survey. To this effect, two kebeles were randomly selected out of the seven kebeles of the town. Likewise, 372 sampled households were selected out of the 5300 total households of the selected kebeles through a stratified simple random sampling technique. Using the statistical model developed by Foster, Greer and Thorbecke, results of the study reveals that 22.4 percent of sample households fall below the poverty line. Likewise, poverty gap and severity were 4.5 and 1.6 percent, respectively. Result of the regression model reveals that sex of household, family size, educational status, dependency ratio, shelter ownership, persons per room and household shocks were the determinants of poverty in the study area. The study result is relevant to inform policy interventions. As poverty in the study town is worse than the national urban centers, the government of Ethiopia, hand-in-hand with the local government, should address the socioeconomic and demographic challenges that intensify poverty.